Pharmacologic Therapies to Promote Recovery of Consciousness - Barra, Megan E.; Edlow, Brian L.; Brophy, Gretchen M. (Seminars in Neurology, 2022)
Pharmacologic interventions are commonly used to support rehabilitation efforts of patients with disorders of consciousness (DoC). The 2018 practice guidelines recommend amantadine in adults with traumatic DoC to promote functional recovery, though several other stimulants are used off-label in clinical practice and trials, such as methylphenidate, bromocriptine, levodopa, and zolpidem. Differences in the mechanisms of action, adverse effects, pharmacokinetics, and drug–drug interactions should be considered when selecting the best agent for each individual patient. Overall, pharmacologic stimulants may provide a safe and inexpensive pathway to increased functionality and participation in rehabilitation. This article provides a concise summary of scientific evidence supporting the use of pharmacologic therapies to stimulate recovery of consciousness in patients with DoC.
Keywords: stimulant; brain injury; consciousness; recovery; neurotransmitter